2011
DOI: 10.1590/s0102-36162011000600004
|View full text |Cite
|
Sign up to set email alerts
|

Regeneração de nervos periféricos: terapia celular e fatores neurotróficos

Abstract: Peripheral nerve trauma results in functional loss in the innervated organ, and recovery without surgical intervention is rare. Many surgical techniques can be used for nerve repair. Among these, the tubulization technique can be highlighted: this allows regenerative factors to be introduced into the chamber. Cell therapy and tissue engineering have arisen as an alternative for stimulating and aiding peripheral nerve regeneration. Therefore, the aim of this review was to provide a survey and analysis on the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 83 publications
0
5
0
1
Order By: Relevance
“…The evidence suggested that dizocine combined with ropivacaine has a significant analgesic effect in rat model of peripheral nerve compression. Peripheral nerve damage directly affects muscle tissue because they disrupt neuromuscular communication and results in loss of function of the innervating organs and cause muscle fiber cross-section and muscle diameter decrease [15][16][17]. Chronic sciatic nerve compression is characterized by variable degree of degeneration in great myelinated axons and endoneural edema [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence suggested that dizocine combined with ropivacaine has a significant analgesic effect in rat model of peripheral nerve compression. Peripheral nerve damage directly affects muscle tissue because they disrupt neuromuscular communication and results in loss of function of the innervating organs and cause muscle fiber cross-section and muscle diameter decrease [15][16][17]. Chronic sciatic nerve compression is characterized by variable degree of degeneration in great myelinated axons and endoneural edema [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The influence of PRP in enhancing axon regeneration has been proposed to result from platelet-released neurotrophic and other factors [214][215][216][217]. An additional platelet potential contributor to enhanced axon regeneration is VEGF, which, as discussed earlier, induces enhanced axon regeneration by inducing rapid vascularization of the entire nerve gap [218,219].…”
Section: Novel Techniquementioning
confidence: 97%
“…Bridging a rat sciatic nerve gap with a PRP-filled silicon tube [198,211] or surrounding the sciatic nerve anastomosis site with a PRP-saturated membrane [212] enhances axon regeneration. In rabbits, filling vein grafts with PRP induces significant axon regeneration compared to empty vein grafts [198,206,[213][214][215].…”
Section: Novel Techniquementioning
confidence: 99%
“…15 Emerging studies have shown that many growth factors, especially many neurotrophic factors such as nerve growth factor (Ngf) and brain-derived neurotrophic factor (Bdnf), are very critical for the development and regeneration of the nervous system. [16][17][18][19] However, there is no systemical investigation of the involvement of growth factors in the biological processes of peripheral nerve injury and repair. In our previous study, by using RNA deep sequencing, we fully determined gene expressions in the sciatic nerve stumps at 0 h, 1 d, 4 d, 7 d, and 14 d aer rat sciatic nerve crush injury and proled differentially expressed genes.…”
Section: Introductionmentioning
confidence: 99%